PERAN MODAL SOSIAL DALAM PENGARUSUTAMAAN GENDER PADA KALANGAN MUSLIMAT NAHDLATUL WATHAN - Rohmi Djalilah, Khirjan Nahdi sitti (Jurnal Review Politik, 2016)
This article aims to find a concrete social capital that is important for gender equality development in Muslimat Nahdlatul Wathan (NW) and to find a new reconstruction of gender issue and its relation to social dynamic. The whole process of this research conducted based on ethno- graphic steps. The results shows that reality of gender in Muslimat NW could be reconstructed into four forms; 1) description through educati- onal process; 2) balance role distribution of public domain; 3) gender’ status gets more autonomy in its organisation, and 4) the relation bet- ween man and women individually and organisationally Secondly, the construction model of gender relation in Muslimat NW some strategic social capital: 1) the equality as a social capital; 2) autonomic status as social capital that helps women to get and admission and become more self-directed (independent) and 3) futuristic thinking as a social capital. A dynamic context makes Muslimat NW become more flexible in making decision for their future ogranisation.